NON-VIOLENCE PRINCIPLES IN KING’S SPEECHES AND ITS IMPACTS TO AFRICAN AMERICAN SOCIETY - Eryn Gemala Putri (Rubikon : Journal of Transnational American Studies, 2015)
This paper is aimed to analyze the non-violence principles in Martin Luther King’s speeches and the impacts to African American society and reveal the consistency of King in practicing non-violence principles. This study is a qualitative research, which is conducted under a library research. To describe and analyze non-violence principles in King’s speeches, the writer applied American Studies perspective of interdisciplinary approach. Therefore, it applies a number of related approaches in an integrated way: literature, social, and culture. The result of this research reveals that Martin Luther King is consistent in applying non-violence principles. Applying non-violence principles gives impacts to African American society. Desegregation in public facility and the legalization of voting right for African American society are the impacts of non-violence principles that initiated by King.Keyword: non-violence principles, impacts of non-violence principles, public desegregation,speech.